Efficacy of novel bacterial consortia in degrading fipronil and thiobencarb in paddy soil: a survey for community structure and metabolic pathways - Faridy, Nastaran; Torabi, Ehssan; Pourbabaee, Ahmad Ali; Osdaghi, Ebrahim; Talebi, Khalil (Frontiers in Microbiology, 2024)
Introduction Fipronil (FIP) and thiobencarb (THIO) represent widely utilized pesticides in paddy fields, presenting environmental challenges that necessitate effective remediation approaches. Despite the recognized need, exploring bacterial consortia efficiently degrading FIP and THIO remains limited. Methods This study isolated three unique bacterial consortia—FD, TD, and MD—demonstrating the capability to degrade FIP, THIO, and an FIP + THIO mixture within a 10-day timeframe. Furthermore, the bioaugmentation abilities of the selected consortia were evaluated in paddy soils under various conditions. Results Sequencing results shed light on the consortia’s composition, revealing a diverse bacterial population prominently featuring Azospirillum, Ochrobactrum, Sphingobium, and Sphingomonas genera. All consortia efficiently degraded pesticides at 800 µg/mL concentrations, primarily through oxidative and hydrolytic processes. This metabolic activity yields more hydrophilic metabolites, including 4-(Trifluoromethyl)-phenol and 1,4-Benzenediol, 2-methyl-, for FIP, and carbamothioic acid, diethyl-, S-ethyl ester, and Benzenecarbothioic acid, S-methyl ester for THIO. Soil bioaugmentation tests highlight the consortia’s effectiveness, showcasing accelerated degradation of FIP and THIO—individually or in a mixture—by 1.3 to 13-fold. These assessments encompass diverse soil moisture levels (20 and 100% v/v), pesticide concentrations (15 and 150 µg/g), and sterile conditions (sterile and non-sterile soils). Discussion This study offers an understanding of bacterial communities adept at degrading FIP and THIO, introducing FD, TD, and MD consortia as promising contenders for bioremediation endeavors.